2009
DOI: 10.1016/j.cmet.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Apoptosis and Plaque Necrosis in Advanced Atherosclerotic Lesions of Apoe−/− and Ldlr−/− Mice Lacking CHOP

Abstract: SUMMARY Endoplasmic reticulum (ER) stress is a hallmark of advanced atherosclerosis, but its causative role in plaque progression is unknown. In-vitro studies have implicated the ER stress effector CHOP in macrophage apoptosis, a process involved in plaque necrosis in advanced atheromata. To test the effect of CHOP deficiency in vivo, aortic root lesions of fat-fed Chop+/+;Apoe−/− and Chop−/−;Apoe−/− mice were analyzed for size and morphology. Despite similar plasma lipoproteins, lesion area was 35% smaller in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
303
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(320 citation statements)
references
References 35 publications
15
303
1
1
Order By: Relevance
“…33 It's implication in atherosclerosis has been recently reported in mice double knock down for CHOP and ApoE, which exhibit a lower extent of atherosclerotic lesions, and less necrotic regions within the plaque. 34 These data suggest that ER stress and particularly CHOP, may promote cell death within the vascular wall and atherosclerosis. Interestingly, HMEC-1 cells silenced for CHOP by siRNA, or fibroblasts issued from CHOP-/-mice, 32 were partly resistant to the cytotoxic effect of oxLDLs, which supports a role for ER stress and CHOP in oxLDLs-mediated apoptosis, in agreement with Tabas et al 34 Moreover, we show that HDLs inhibit the phosphorylation of JNK induced by oxLDLs, which in our system is activated by IRE1a, and is involved in ER stress-dependent apoptosis 9, via the JNK proapoptotic pathway, as reported.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…33 It's implication in atherosclerosis has been recently reported in mice double knock down for CHOP and ApoE, which exhibit a lower extent of atherosclerotic lesions, and less necrotic regions within the plaque. 34 These data suggest that ER stress and particularly CHOP, may promote cell death within the vascular wall and atherosclerosis. Interestingly, HMEC-1 cells silenced for CHOP by siRNA, or fibroblasts issued from CHOP-/-mice, 32 were partly resistant to the cytotoxic effect of oxLDLs, which supports a role for ER stress and CHOP in oxLDLs-mediated apoptosis, in agreement with Tabas et al 34 Moreover, we show that HDLs inhibit the phosphorylation of JNK induced by oxLDLs, which in our system is activated by IRE1a, and is involved in ER stress-dependent apoptosis 9, via the JNK proapoptotic pathway, as reported.…”
Section: Discussionmentioning
confidence: 91%
“…34 These data suggest that ER stress and particularly CHOP, may promote cell death within the vascular wall and atherosclerosis. Interestingly, HMEC-1 cells silenced for CHOP by siRNA, or fibroblasts issued from CHOP-/-mice, 32 were partly resistant to the cytotoxic effect of oxLDLs, which supports a role for ER stress and CHOP in oxLDLs-mediated apoptosis, in agreement with Tabas et al 34 Moreover, we show that HDLs inhibit the phosphorylation of JNK induced by oxLDLs, which in our system is activated by IRE1a, and is involved in ER stress-dependent apoptosis 9, via the JNK proapoptotic pathway, as reported. 40 The effect of oxLDLs and HDLs on ER stress-induced apoptosis is also favoured by caspase-12 processing that occurs upon oxLDLs stimulation and which is inhibited by HDLs in murine 25 However, the precise role of caspase-12 in human is still undefined and need further investigation as human caspase-12 gene encodes an aberrant caspase.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the reduction in plaque size that we observed in our study is likely to result from IRE1 inhibitor-mediated antiinflammatory changes and not to result from the product of changes in lipid metabolism. Although we have seen important gains in mitigating atherosclerosis by pharmacologically targeting IRE1 in our experimental models, it is important to note that the other UPR branches, particularly the PERK-CHOP branch, are also induced as atherosclerosis progresses and seem to be instrumental for macrophage apoptosis (5,11). Previous studies focusing on the engagement of apoptotic pathways initiated by the UPR (such as those mediated by CHOP and JNK) showed that mice deficient for these apoptotic effectors are protected from atherosclerosis (5,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 91%
“…Although we have seen important gains in mitigating atherosclerosis by pharmacologically targeting IRE1 in our experimental models, it is important to note that the other UPR branches, particularly the PERK-CHOP branch, are also induced as atherosclerosis progresses and seem to be instrumental for macrophage apoptosis (5,11). Previous studies focusing on the engagement of apoptotic pathways initiated by the UPR (such as those mediated by CHOP and JNK) showed that mice deficient for these apoptotic effectors are protected from atherosclerosis (5,(11)(12)(13). Independent of CHOP or JNK engagement, here, we found that modulating IRE1 signaling in vivo with small molecule IRE1 inhibitors modifies a different branch of UPR signaling that impinges on metaflammation and alters the course of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation